2021
DOI: 10.3389/fphar.2021.611610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Ratios of Yinchen and Gancao Decoction on ANIT-Treated Cholestatic Liver Injury in Mice and Its Potential Underlying Mechanism

Abstract: Cholestasis is a pathological state that leads to serious liver disease; however, therapeutic options remain limited. Yinchen and Gancao are often used in combination at different ratios in traditional Chinese formulae for the treatment of jaundice and cholestasis. In the present study, we investigated the effect of decoctions containing different ratios of Yinchen and Gancao (YGD) on alpha-naphthyl isothiocyanate (ANIT)-treated intrahepatic cholestasis (IC) in mice, and further explored the underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Glycyrrhizae, also known as licorice, is the most frequently used Chinese herb or food additive ( Yu et al, 2018 ). We found that a glycyrrhizae decoction prepared from licorice root protected against ANIT-induced cholestatic liver injury of mice through inhibition of the TLRs/NF-κB signaling pathway ( Su et al, 2021 ). Glycyrrhizin is the principal triterpene component of the glycyrrhizae decoction, and it is mainly metabolized to glycyrrhetinic acid (GA) through the intestinal flora ( Akao et al, 1994 ; Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycyrrhizae, also known as licorice, is the most frequently used Chinese herb or food additive ( Yu et al, 2018 ). We found that a glycyrrhizae decoction prepared from licorice root protected against ANIT-induced cholestatic liver injury of mice through inhibition of the TLRs/NF-κB signaling pathway ( Su et al, 2021 ). Glycyrrhizin is the principal triterpene component of the glycyrrhizae decoction, and it is mainly metabolized to glycyrrhetinic acid (GA) through the intestinal flora ( Akao et al, 1994 ; Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that a glycyrrhizae decoction prepared from licorice root protected against ANIT-induced cholestatic liver injury of mice through inhibition of the TLRs/NF-κB signaling pathway ( Su et al, 2021 ). Glycyrrhizin is the principal triterpene component of the glycyrrhizae decoction, and it is mainly metabolized to glycyrrhetinic acid (GA) through the intestinal flora ( Akao et al, 1994 ; Su et al, 2021 ). Due to high exposure in the liver and a good therapeutic effect, GA can be a potent agent for cholestasis treatment in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…FuZi, the monarch drug of another TCM formula Fuzi Lizhong decoction, exerted protective effects against non-alcoholic fatty liver disease (NAFLD) through anti-inflammatory responses ( Yang et al, 2018 ; Yang et al, 2020 ). Single Yinchen or the combination of Yinchen with other herbs could protect against hepatocyte apoptosis ( Zhang et al, 2022a ), non-alcoholic fatty liver disease ( Guo et al, 2017 ), or ANIT-induced cholestatic liver injury ( Su et al, 2021 ). Compounds such as salvianolic acid C ( Wu et al, 2019 ) and salvianolic acid A protect against drug-induced acute liver failure or CCl 4 -induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological research further confirms the role of ALB in regulating inflammation, where it reduces the production of inflammatory mediators and modulates inflammatory responses [30]. TNF, as a vital inflammatory regulatory factor associated with Toll-like receptor 4 (TLR4) activation, induces the release of pro-inflammatory cytokines, thereby promoting the occurrence of jaundice and its inflammatory complications [31]. Therefore, we hypothesize that MG and WG may exert their effects in the treatment of jaundice and related liver diseases by modulating inflammatory factors.…”
Section: Analysis Of Protein-protein Interaction (Ppi) Network and Se...mentioning
confidence: 97%